Formulation and nutritional quality of plant-based cheese sold in Italy - Andrea Bresciani; Paola Biscotti; Donato Angelino; Cristian Del Bo’; Nicoletta Pellegrini; Patrizia Riso; Alessandra Marti; Daniela Martini (Applied Food Research)
The production and consumption of plant-based products which resemble animal counterparts, among which cheese-analogues, is constantly increasing. For this reason, there is the need for assessing their nutritional composition and ingredients, which might help in understanding the relation between formulation and composition, enhancing product development, and driving conscious and healthy food choices.The present study aims to evaluate plant-based cheese (PBC) currently on the Italian market, in terms of nutritional quality (i.e., energy, nutrient and salt content) and ingredients used for their formulation. To this purpose, data from the labelling of 127 PBC (49 analogues of conventional cheese (ACC), 62 tofu and 16 tempeh) were collected. Median and interquartile range values were calculated for the energy, nutrients and salt, whereas minimum, maximum and mode of the number of ingredients, as well as the most used ingredients, were considered for each product category.The number of ingredients in cheese analogues varied from 1 to 17 and largely differed among and between categories, with ACC usually having the most complex and heterogeneous formulations. Significant differences were observed among categories for energy and most nutrients, with ACC showing the highest content in salt, total fat, and saturates (p < 0.05). Although some relations between formulation and nutritional quality have been highlighted, a clear cluster of products described by the considered variables was not shown.This study sheds light on the nutritional quality and formulation of PBC on the market and provides the basis for driving future innovations.